Asymmetric semi-solid electrolyte diaphragm and preparation method thereof

By using a combination of active and inert skeletons in asymmetric semi-solid electrolyte membranes and combining hot pressing technology, the problems of insufficient support and poor bending resistance of the existing membrane are solved, and higher ionic conductivity and mechanical strength are achieved, ensuring the safety and performance of the battery.

CN119695398APending Publication Date: 2025-03-25SINOMA LITHIUM BATTERY SEPARATOR CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411929511.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing asymmetric semi-solid electrolyte membranes have insufficient support and cannot adapt to bending, and the overall bending resistance is poor.

Method used

Asymmetric semi-solid electrolyte membrane is made of polymer matrix, inorganic filler, lithium salt and skeleton materials. The fast ion transport layer uses an active skeleton, the stable layer uses an inert skeleton, and a composite membrane is formed by hot pressing.

Benefits of technology

The ionic conductivity and mechanical strength of the film are improved, the overall bending resistance is enhanced, and the safety and electrical performance of the battery are ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005209930510000101
    Figure BDA0005209930510000101
  • Figure BDA0005209930510000112
    Figure BDA0005209930510000112
  • Figure HDA0005209930520000011
    Figure HDA0005209930520000011
Patent Text Reader

Abstract

The invention discloses an asymmetric semi-solid electrolyte diaphragm and a preparation method thereof, and belongs to the technical field of lithium batteries. The asymmetric semi-solid electrolyte diaphragm comprises a rapid ion transport layer facing a positive electrode layer and a stable layer facing a negative electrode layer, the rapid ion transport layer and the stable layer are both prepared from a polymer matrix, an inorganic filler, a lithium salt and a skeleton, the rapid ion transport layer adopts an active skeleton, and the stable layer adopts an inert skeleton. According to the asymmetric semi-solid electrolyte diaphragm and the preparation method thereof, the problem that an existing diaphragm is poor in bending resistance is solved, the rapid ion transmission layer adopts an active framework, the framework forms a continuous lithium ion channel, and the ionic conductivity is remarkably improved; and an inert skeleton used by the stable layer is made of a high polymer material and is used for improving the mechanical property of the solid electrolyte membrane, so that the overall bending resistance of the asymmetric semi-solid electrolyte membrane is stronger.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, in particular to an asymmetric semi-solid electrolyte membrane and a preparation method thereof. Background Art

[0002] The core of all-solid-state lithium battery technology lies in the innovation of electrolytes, and the ultimate goal is to achieve all-solid electrolytes. However, with the continuous increase in battery energy density requirements, technical challenges such as ion conductivity and interface are also increasing. Semi-solid lithium batteries can be used as an important transition technology for all-solid-state batteries. By adding a certain amount of liquid electrolyte to the all-solid electrolyte, the ion conductivity and interface impedance of the solid electrolyte are improved on the basis of giving full play to the advantages of the solid electrolyte, thus giving rise to semi-solid lithium battery electrolytes.

[0003] The Chinese patent with publication number CN111009683B discloses an asymmetric semi-solid electrolyte, preparation method and metal lithium secondary battery, which is formed by coating different solid electrolyte components on both sides of the diaphragm, and the electrolyte membrane facing the positive electrode is composed of lithium salt, polymer matrix that can conduct lithium ions and inorganic ceramic powder, and the electrolyte membrane facing the negative electrode is a gel electrolyte formed by polymer and pore-forming agent. The overall support force of the asymmetric structure in the patent is insufficient and cannot be used for bending. Summary of the invention

[0004] The object of the present invention is to provide an asymmetric semi-solid electrolyte membrane and a preparation method thereof, thereby solving the problems raised in the above-mentioned background technology.

[0005] To achieve the above-mentioned purpose, the present invention provides the following technical solution: an asymmetric semi-solid electrolyte membrane, comprising a fast ion transport layer facing the positive electrode layer and a stabilizing layer facing the negative electrode, wherein the fast ion transport layer and the stabilizing layer are both made of a polymer matrix, an inorganic filler, a lithium salt and a skeleton, wherein the fast ion transport layer adopts an active skeleton, and the stabilizing layer adopts an inert skeleton, and the fast ion transport layer and the stabilizing layer are bonded by hot pressing.

[0006] Preferably, the preparation method of the active skeleton is as follows:

[0007] Prepare the precursor solution of LLTO, dissolve the precursor material of LLTO in the solvent in proportion, add an appropriate amount of PVA to the LLTO precursor solution as a polymer matrix, PVA can help form a stable gel structure, add an appropriate amount of cross-linking agent and initiator to promote the formation of gelation, let the solution gel, and form a 3D nanostructured LLTO hydrogel; the formed LLTO hydrogel is heat-treated in air at 800°C for 2 hours, the purpose of which is to remove organic components and crystallize LLTO to form a porous active skeleton.

[0008] Preferably, the LLTO precursor material includes but is not limited to LiNO3, La(NO3)3·6H2O and Ti(OBu)4, the solvent for dissolving the LLTO precursor material is deionized water, the cross-linking agent is boric acid, and the initiator is one of ammonium persulfate and potassium persulfate.

[0009] Preferably, the preparation method of the inert skeleton is as follows: dissolving PI, uniformly coating the prepared PI solution on a substrate, drying naturally at room temperature, removing the solvent to form a PI film, and heat treating the PI film at 200-300°C for 2 hours to improve the mechanical strength and chemical stability of the PI film to form an inert skeleton.

[0010] Preferably, the material for dissolving PI is selected from one of N-methylpyrrolidone and dimethylformamide, and the substrate is glass or silicon wafer.

[0011] Preferably, the polymer matrix is ​​at least one of PEO, PVDF, PAN, PPO, PP, PE, PS and PMMA.

[0012] Preferably, the materials used to prepare the fast ion transport layer and the stabilizing layer also include a plasticizer, and the plasticizer is at least one of PC, DMSO, and EG.

[0013] Preferably, the inorganic filler is at least one of SiO2 nanoparticles, Al2O3 nanoparticles, montmorillonite, ZrO2 and TiO2.

[0014] Preferably, the lithium salt is at least one of LiPF6, LiTFSI, LiBF4, LiClO4 and LiFSI.

[0015] Another technical problem to be solved by the present invention is to provide a method for preparing an asymmetric semi-solid electrolyte membrane, comprising the following steps:

[0016] Step 1: dissolving the polymer, inorganic filler and lithium salt in a predetermined ratio to prepare an electrolyte solution for a fast ion transport layer, and injecting the electrolyte solution into the active skeleton to form a fast ion transport layer supported by the skeleton;

[0017] Step 2: dissolving the polymer, inorganic filler and lithium salt in a predetermined ratio to prepare an electrolyte solution for the stabilizing layer, and injecting the electrolyte solution into the inert skeleton to form a stabilizing layer supported by the skeleton;

[0018] Step 3: Laminating the fast ion transport layer and the stabilization layer together by hot pressing to form a final composite membrane.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] 1. An asymmetric semi-solid electrolyte membrane and a preparation method thereof proposed in the present invention adopt a polymer matrix material with a specific component and ratio and an inorganic filler to form a semi-solid electrolyte, and an asymmetric structure is designed, with a thicker stabilizing layer on one side and a thinner fast ion transport layer on the other side. The fast ion transport layer adopts a higher plasticizer content to help improve the plasticity of the membrane, thereby improving the ion conductivity, and a higher inorganic filler content helps to enhance the mechanical strength and thermal stability of the membrane, improve the overall rigidity and heat resistance of the membrane, and a higher plasticizer content helps to form a more uniform interface and also helps to inhibit the formation of lithium dendrites; the stabilizing layer adopts a lower plasticizer content and a higher inorganic filler content to help improve the mechanical strength and thermal stability of the membrane, ensuring that the membrane has sufficient flexibility and high ion conductivity, and a higher inorganic filler content helps to form a denser structure, which helps to inhibit the growth of lithium dendrites and improve the safety of the battery;

[0021] 2. The present invention proposes an asymmetric semi-solid electrolyte membrane and a preparation method thereof, wherein support structures are added to the fast ion transport layer and the stabilizing layer respectively. The fast ion transport layer adopts an active skeleton and has ion conductivity. The skeleton forms a continuous lithium ion channel, and the ion conductivity is significantly improved. The inert skeleton used in the stabilizing layer is composed of a polymer material and does not have ion transport capability. It is used to improve the mechanical properties of the solid electrolyte membrane, thereby making the overall anti-bending performance of the asymmetric semi-solid electrolyte membrane stronger. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION

[0023] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Embodiment 1:

[0025] In order to solve the problem of insufficient support and poor bending resistance of existing asymmetric semi-solid electrolyte diaphragms, please refer to Figure 1 , this embodiment provides the following technical solutions:

[0026] An asymmetric semi-solid electrolyte membrane includes a fast ion transport layer facing the positive electrode layer and a stabilizing layer facing the negative electrode. The fast ion transport layer and the stabilizing layer are both made of a polymer matrix, an inorganic filler, a lithium salt and a skeleton. The fast ion transport layer uses an active skeleton and the stabilizing layer uses an inert skeleton. The fast ion transport layer and the stabilizing layer are bonded by hot pressing.

[0027] The preparation method of the active skeleton is as follows:

[0028] The materials LiNO3, La(NO3)3·6H2O and Ti(OBu)4 for preparing the precursor solution of LLTO are dissolved in ion water in proportion, and an appropriate amount of PVA is added to the LLTO precursor solution as a polymer matrix. PVA can help form a stable gel structure. An appropriate amount of boric acid and ammonium sulfate are added to promote the formation of gelation, so that the solution is gelled to form a 3D nanostructured LLTO hydrogel; the formed LLTO hydrogel is heat treated in air at 800°C for 2 hours to remove organic components and crystallize LLTO to form a porous active skeleton.

[0029] The preparation method of the inert skeleton is as follows: dissolving the PI material in N-methylpyrrolidone to prepare a PI solution, uniformly coating the prepared PI solution on glass, drying it naturally at room temperature, removing the solvent, forming a PI film, and heat treating the PI film at 200-300°C for 2 hours to improve the mechanical strength and chemical stability of the PI film to form an inert skeleton.

[0030] The asymmetric semi-solid electrolyte membrane was prepared using the following ingredients:

[0031] Fast ion transport layer, thickness: 10 μm, composition as follows:

[0032] PEO: 10wt%

[0033] PC: 40wt%

[0034] LiPF6: 5wt%

[0035] SiO2: 5wt%

[0036] Active skeleton: 40wt%;

[0037] Stabilization layer, thickness: 30 μm, composition:

[0038] PEO: 20wt%

[0039] PC: 10wt%

[0040] LiPF6: 5wt%

[0041] SiO2: 60wt%

[0042] Inert skeleton: 5wt%.

[0043] In order to better demonstrate the preparation process of an asymmetric semi-solid electrolyte membrane, this embodiment now proposes a method for preparing an asymmetric semi-solid electrolyte membrane, comprising the following steps:

[0044] Step 1: Dissolve PEO, PC, LiPF6 and SiO2 in N,N-dimethylformamide in proportion to prepare an electrolyte solution for a fast ion transport layer, inject the electrolyte solution into the active skeleton by dipping twice and spraying the remaining material, and dry it to form a fast ion transport layer supported by the skeleton;

[0045] Step 2: PEO, PC, LiPF6 and SiO2 are dissolved in N,N-dimethylformamide in proportion to prepare an electrolyte solution of a stabilizing layer, and the electrolyte solution is injected into the inert skeleton by spraying, and dried to form a stabilizing layer supported by the skeleton;

[0046] Step 3: Laminating the fast ion transport layer and the stabilization layer together by hot pressing to form a final composite membrane.

[0047] Embodiment 2:

[0048] Take PEO: 15wt%, PC: 40wt%, LiPF6: 5wt%, SiO2: 5wt% and dissolve them in N,N-dimethylformamide to prepare an electrolyte solution for a fast ion transport layer, and use the method of Example 1 to prepare an active skeleton, take 45wt% of the active skeleton as a supporting skeleton, and immerse it in the electrolyte solution. After immersion twice, spray the remaining electrolyte solution onto the active skeleton, and form a fast ion transport layer supported by the skeleton after drying. The fast ion transport layer after drying has a thickness of 12μm.

[0049] PEO: 20wt%, PC: 10wt%, LiPF6: 5wt%, SiO2: 60wt% were dissolved in N,N-dimethylformamide to prepare an electrolyte solution for a stabilizing layer. The electrolyte solution was injected into the inert skeleton by spraying, and after drying, a stabilizing layer supported by the skeleton was formed. The thickness of the stabilizing layer was 35μm.

[0050] The fast ion transport layer and the stabilizing layer are laminated together by hot pressing to form the final composite membrane.

[0051] Embodiment 3:

[0052] Take PEO: 10wt%, PC: 40wt%, LiPF6: 5wt%, SiO2: 5wt% and dissolve them in N,N-dimethylformamide to prepare an electrolyte solution for a fast ion transport layer, and use the method of Example 1 to prepare an active skeleton, take 40wt% of the active skeleton as a supporting skeleton, and immerse it in the electrolyte solution. After immersion twice, spray the remaining electrolyte solution onto the active skeleton, and form a fast ion transport layer supported by the skeleton after drying. The fast ion transport layer after drying has a thickness of 10μm.

[0053] Take PEO: 15wt%, PC: 10wt%, LiPF6: 5wt%, SiO2: 60wt% and dissolve them in N,N-dimethylformamide to prepare an electrolyte solution for a stabilizing layer. The same method as in Example 1 is used to prepare an inert skeleton. 10wt% of the inert skeleton is taken as a supporting skeleton. The electrolyte solution is injected into the inert skeleton by spraying. After drying, a stabilizing layer supported by the skeleton is formed. The thickness of the stabilizing layer is 36μm.

[0054] The fast ion transport layer and the stabilizing layer are laminated together by hot pressing to form the final composite membrane.

[0055] Embodiment 4:

[0056] PVDF: 15wt%, DMSO: 30wt%, LiTFSI: 5wt%, Al2O3: 10wt% were dissolved in N,N-dimethylformamide to prepare an electrolyte solution for a fast ion transport layer, and an active skeleton was prepared by the method of Example 1, 40wt% of the active skeleton was taken as a supporting skeleton and immersed in the electrolyte solution. After two immersions, the remaining electrolyte solution was sprayed onto the active skeleton, and a fast ion transport layer supported by a skeleton was formed after drying. The fast ion transport layer after drying had a thickness of 12μm.

[0057] PVDF: 25wt%, DMSO: 15wt%, LiTFSI: 5wt%, Al2O3: 50wt% were dissolved in N,N-dimethylformamide to prepare an electrolyte solution for a stabilizing layer. An inert skeleton was prepared by the same method as in Example 1. 5wt% of the inert skeleton was used as a supporting skeleton. The electrolyte solution was injected into the inert skeleton by spraying. After drying, a stabilizing layer supported by the skeleton was formed. The thickness of the stabilizing layer was 38μm.

[0058] The fast ion transport layer and the stabilizing layer are laminated together by hot pressing to form the final composite membrane.

[0059] Embodiment 5:

[0060] PVDF: 20wt%, DMSO: 30wt%, LiTFSI: 5wt%, Al2O3: 10wt% were dissolved in N,N-dimethylformamide to prepare an electrolyte solution for a fast ion transport layer, and an active skeleton was prepared by the method of Example 1, 35wt% of the active skeleton was taken as a supporting skeleton and immersed in the electrolyte solution. After two immersions, the remaining electrolyte solution was sprayed onto the active skeleton, and a fast ion transport layer supported by a skeleton was formed after drying. The fast ion transport layer after drying had a thickness of 10μm.

[0061] PVDF: 25wt%, DMSO: 15wt%, LiTFSI: 5wt%, Al2O3: 50wt% were dissolved in N,N-dimethylformamide to prepare an electrolyte solution for a stabilizing layer. An inert skeleton was prepared by the same method as in Example 1. 5wt% of the inert skeleton was used as a supporting skeleton. The electrolyte solution was injected into the inert skeleton by spraying. After drying, a stabilizing layer supported by the skeleton was formed. The thickness of the stabilizing layer was 38μm.

[0062] The fast ion transport layer and the stabilizing layer are laminated together by hot pressing to form the final composite membrane.

[0063] Embodiment 6:

[0064] PVDF: 15wt%, DMSO: 30wt%, LiTFSI: 5wt%, Al2O3: 10wt% were dissolved in N,N-dimethylformamide to prepare an electrolyte solution for a fast ion transport layer, and an active skeleton was prepared by the method of Example 1, 40wt% of the active skeleton was taken as a supporting skeleton and immersed in the electrolyte solution. After two immersions, the remaining electrolyte solution was sprayed onto the active skeleton, and a fast ion transport layer supported by a skeleton was formed after drying. The fast ion transport layer after drying had a thickness of 12μm.

[0065] PVDF: 20wt%, DMSO: 15wt%, LiTFSI: 5wt%, Al2O3: 50wt% were dissolved in N,N-dimethylformamide to prepare an electrolyte solution for a stabilizing layer. An inert skeleton was prepared by the same method as in Example 1. 10wt% of the inert skeleton was used as a supporting skeleton. The electrolyte solution was injected into the inert skeleton by spraying. After drying, a stabilizing layer supported by the skeleton was formed. The thickness of the stabilizing layer was 36μm.

[0066] The fast ion transport layer and the stabilizing layer are laminated together by hot pressing to form the final composite membrane.

[0067] Embodiment 7:

[0068] PAN: 10wt%, EG: 40wt%, LiClO4: 5wt%, montmorillonite: 5wt% were dissolved in N,N-dimethylformamide to prepare an electrolyte solution for a fast ion transport layer, and an active skeleton was prepared by the method of Example 1, 40wt% of the active skeleton was taken as a supporting skeleton and immersed in the electrolyte solution. After two immersions, the remaining electrolyte solution was sprayed onto the active skeleton, and a fast ion transport layer supported by a skeleton was formed after drying. The fast ion transport layer after drying had a thickness of 15μm.

[0069] PAN: 20wt%, EG: 10wt%, LiClO4: 5wt%, montmorillonite: 60wt% were dissolved in N,N-dimethylformamide to prepare an electrolyte solution for a stabilizing layer. An inert skeleton was prepared by the same method as in Example 1. 5wt% of the inert skeleton was used as a supporting skeleton. The electrolyte solution was injected into the inert skeleton by spraying. After drying, a stabilizing layer supported by the skeleton was formed. The thickness of the stabilizing layer was 35μm.

[0070] The fast ion transport layer and the stabilizing layer are laminated together by hot pressing to form the final composite membrane.

[0071] Embodiment 8:

[0072] PAN: 15wt%, EG: 40wt%, LiClO4: 5wt%, montmorillonite: 5wt% were dissolved in N,N-dimethylformamide to prepare an electrolyte solution for a fast ion transport layer, and an active skeleton was prepared by the method of Example 1, 35wt% of the active skeleton was taken as a supporting skeleton and immersed in the electrolyte solution. After two immersions, the remaining electrolyte solution was sprayed onto the active skeleton, and a fast ion transport layer supported by a skeleton was formed after drying. The fast ion transport layer after drying had a thickness of 14μm.

[0073] PAN: 20wt%, EG: 10wt%, LiClO4: 5wt%, montmorillonite: 60wt% were dissolved in N,N-dimethylformamide to prepare an electrolyte solution for a stabilizing layer. An inert skeleton was prepared by the same method as in Example 1. 5wt% of the inert skeleton was used as a supporting skeleton. The electrolyte solution was injected into the inert skeleton by spraying. After drying, a stabilizing layer supported by the skeleton was formed. The thickness of the stabilizing layer was 35μm.

[0074] The fast ion transport layer and the stabilizing layer are laminated together by hot pressing to form the final composite membrane.

[0075] Embodiment 9:

[0076] PAN: 10wt%, EG: 40wt%, LiClO4: 5wt%, montmorillonite: 5wt% were dissolved in N,N-dimethylformamide to prepare an electrolyte solution for a fast ion transport layer, and an active skeleton was prepared by the method of Example 1, 40wt% of the active skeleton was taken as a supporting skeleton and immersed in the electrolyte solution. After two immersions, the remaining electrolyte solution was sprayed onto the active skeleton, and a fast ion transport layer supported by a skeleton was formed after drying. The fast ion transport layer after drying had a thickness of 15μm.

[0077] PAN: 15wt%, EG: 10wt%, LiClO4: 5wt%, montmorillonite: 60wt% were dissolved in N,N-dimethylformamide to prepare an electrolyte solution for a stabilizing layer. An inert skeleton was prepared by the same method as in Example 1. 10wt% of the inert skeleton was used as a supporting skeleton. The electrolyte solution was injected into the inert skeleton by spraying. After drying, a stabilizing layer supported by the skeleton was formed. The thickness of the stabilizing layer was 36μm.

[0078] The fast ion transport layer and the stabilizing layer are laminated together by hot pressing to form the final composite membrane.

[0079] The asymmetric semi-solid electrolyte membranes manufactured in the above-mentioned Examples 1, 4 and 7 were subjected to bending tests:

[0080] Sample preparation: A semi-solid lithium battery membrane with a size of 100 mm x 50 mm was selected as the test sample;

[0081] Equipment preparation: Use a bending test machine with an adjustable bending radius;

[0082] Environmental conditions: Ensure that the test environment temperature is stable at 25℃±2℃;

[0083] Setting parameters: Set the bending radius to 10mm and the bending angle to 180°;

[0084] Pretreatment: Leave the sample at room temperature for at least 2 hours to ensure that it reaches stable environmental conditions;

[0085] Install the sample: Fix the sample on the testing machine and ensure that the center position of the sample is aligned with the bending axis;

[0086] Start the test: Start the testing machine and perform the bending operation at a constant speed until the sample completes a 180° bend;

[0087] Repeated test: 10 cycles of testing were performed to evaluate the cyclic bending performance.

[0088] The following test data were obtained:

[0089]

[0090]

[0091] It can be concluded from the above table that although different materials are used to prepare the asymmetric semi-solid electrolyte membranes in Example 1, Example 4 and Example 7, the prepared asymmetric semi-solid electrolyte membranes have little difference in performance, and after the bending test, no cracks, peeling, deformation and expansion are found, indicating that the asymmetric semi-solid electrolyte membrane prepared by the present invention has strong bending resistance.

[0092] The sample materials after the bending performance test were used in lithium batteries, and the following data were obtained after testing:

[0093]

[0094] After the bending test, the internal resistance of the asymmetric semi-solid electrolyte membrane prepared in this embodiment changed by less than 15%, the capacity retention rate exceeded 90%, the self-discharge rate was less than 5%, and good electrical performance was still maintained.

[0095] In summary: the present invention proposes an asymmetric semi-solid electrolyte membrane and a preparation method thereof, which adopts a polymer matrix material with a specific component and ratio and an inorganic filler to form a semi-solid electrolyte, and designs an asymmetric structure, with a thicker stabilizing layer on one side and a thinner fast ion transport layer on the other side. The fast ion transport layer adopts a higher plasticizer content, which helps to improve the plasticity of the membrane, thereby improving the ion conductivity. This is because the plasticizer can reduce the interaction between polymer chains and make lithium ions move more easily. The higher inorganic filler content helps to enhance the mechanical strength and thermal stability of the membrane, because the inorganic filler can form a network structure, improve the overall rigidity and heat resistance of the membrane, and the higher plasticizer content helps to form a more uniform interface, which also helps to inhibit the lithium The formation of dendrites; the stabilization layer uses a lower plasticizer content and a higher inorganic filler content, which helps to improve the mechanical strength and thermal stability of the membrane, ensuring that the membrane has sufficient flexibility and high ion conductivity. The higher inorganic filler content helps to form a denser structure, which helps to inhibit the growth of lithium dendrites and improve the safety of the battery; at the same time, support structures are added to the fast ion transport layer and the stabilization layer respectively. The fast ion transport layer uses an active skeleton with ion conductivity. The skeleton forms a continuous lithium ion channel, and the ion conductivity is significantly improved; the inert skeleton used in the stabilization layer is composed of a polymer material and does not have ion transport ability. It is used to improve the mechanical properties of the solid electrolyte membrane, so that the overall anti-bending performance of the asymmetric semi-solid electrolyte membrane is stronger.

[0096] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0097] While the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that many changes, modifications, substitutions and variations can be made to the embodiments without departing from the principles and spirit of the invention.

Claims

1. An asymmetric semi-solid electrolyte membrane, comprising a fast ion transport layer facing the positive electrode layer and a stabilizing layer facing the negative electrode, characterized in that: The fast ion transport layer and the stabilizing layer are both made of a polymer matrix, an inorganic filler, a lithium salt and a skeleton, wherein the fast ion transport layer adopts an active skeleton and the stabilizing layer adopts an inert skeleton, and the fast ion transport layer and the stabilizing layer are bonded by hot pressing.

2. The asymmetric semi-solid electrolyte membrane according to claim 1, characterized in that: The preparation method of the active skeleton is as follows: Prepare a precursor solution of LLTO, dissolve the precursor material of LLTO in a solvent in proportion, add an appropriate amount of PVA to the LLTO precursor solution, add an appropriate amount of a cross-linking agent and an initiator, and gel the solution to form a 3D nanostructured LLTO hydrogel; heat-treat the formed LLTO hydrogel in air at 800°C for 2 hours to form a porous active skeleton.

3. The asymmetric semi-solid electrolyte membrane according to claim 2, characterized in that: The LLTO precursor material includes but is not limited to LiNO3, La(NO3)3·6H2O and Ti(OBu)4, the solvent for dissolving the LLTO precursor material is deionized water, the cross-linking agent is boric acid, and the initiator is one of ammonium persulfate and potassium persulfate.

4. The asymmetric semi-solid electrolyte membrane according to claim 1, characterized in that: The preparation method of the inert skeleton is as follows: dissolving PI, uniformly coating the prepared PI solution on a substrate, drying naturally at room temperature, removing the solvent to form a PI film, and heat treating the PI film at 200-300° C. for 2 hours to form an inert skeleton.

5. The asymmetric semi-solid electrolyte membrane according to claim 4, characterized in that: The material for dissolving PI is selected from one of N-methylpyrrolidone and dimethylformamide, and the substrate is glass or silicon wafer.

6. The asymmetric semi-solid electrolyte membrane according to claim 1, characterized in that: The polymer matrix is ​​at least one of PEO, PVDF, PAN, PPO, PP, PE, PS and PMMA.

7. The asymmetric semi-solid electrolyte membrane according to claim 1, characterized in that: The materials for preparing the fast ion transport layer and the stabilizing layer also include a plasticizer, and the plasticizer is at least one of PC, DMSO, and EG.

8. The asymmetric semi-solid electrolyte membrane according to claim 1, characterized in that: The inorganic filler is at least one of SiO2 nanoparticles, Al2O3 nanoparticles, montmorillonite, ZrO2 and TiO2.

9. The asymmetric semi-solid electrolyte membrane according to claim 1, characterized in that: The lithium salt is at least one of LiPF6, LiTFSI, LiBF4, LiClO4 and LiFSI.

10. A method for preparing an asymmetric semi-solid electrolyte membrane according to any one of claims 1 to 9, characterized in that: The following steps are involved: Step 1: dissolving the polymer, inorganic filler and lithium salt in a predetermined ratio to prepare an electrolyte solution for a fast ion transport layer, and injecting the electrolyte solution into the active skeleton to form a fast ion transport layer supported by the skeleton; Step 2: dissolving the polymer, inorganic filler and lithium salt in a predetermined ratio to prepare an electrolyte solution for the stabilizing layer, and injecting the electrolyte solution into the inert skeleton to form a stabilizing layer supported by the skeleton; Step 3: Laminating the fast ion transport layer and the stabilization layer together by hot pressing to form a final composite membrane.

Citation Information

Patent Citations

  • An asymmetric semi-solid electrolyte, its preparation method, and a lithium metal secondary battery

    CN111009683B